Theoretical Results of Research on Spatial and Territorial Development (on Examples of the North of European Russia) - Lazhentsev, Vitaly Nikolayevich (Economy of Regions, 2015)
The article focuses on the relationship between the concepts of “spatial” and “territorial” development. It is shown that these concepts are different in their content, but at the same time greatly complement each other in the specific studies. Only in the category of “spatial development”, there are general directions of productive forces, the geographical dimension of a certain type of activity, the economic measurement of distances, line communications and other network structure of the economy. The author includes to the concept of “territorial development” the territory itself as an area of natural and economic capital and territorial management based on it. The study of the spatial and territorial aspects of socio-economic development of the European North of Russia has shown that its immediate future is connected not only to the large projects of creation of new fuel and energy, mineral and timber bases but with the improvement of the existing economic systems on the basis of scientific and technological progress and inter-regional integration. The moving from the developed territories to new Arctic and northern locations is associated with huge costs and requires time for scientific and technical preparations. The modernization of existing industries and clusters is a priority in the development of the productive forces of the European North of Russia. Theoretical and practical recommendations as a result of the study of the spatial and territorial development can be applied in the development of state strategic planning documents. Currently, the practice of strategic planning does not fully explain the content of the concepts of “spatial development” and “territorial development”. And this incompleteness is so essential that its overcoming should be seen as one of the major objectives of regional policy.